2013
DOI: 10.1186/1475-2875-12-117
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment with a tetrandrine/chloroquine combination for chloroquine-resistant falciparum malaria in Aotus monkeys

Abstract: BackgroundIn vitro evidence indicates that tetrandrine (TT) can potentiate the action of chloroquine 40-fold against choloquine-resistant Plasmodium falciparum. The key question emanating from that study is “would tetrandine and chloroquine be highly effective in a live Aotus monkey model with chloroquine-resistant parasites”. This study was designed to closely mimic the pharmacological/anti-malarial activity in man.MethodsThe Vietnam Smith/RE strain of P. falciparum, which is chloroquine-resistant was used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Owl monkeys have been used extensively in the study of malaria, including maintenance of various malarial strains, antigen production, studies of host-vector relationships, parasite life-cycles, and potential therapeutics (Aikawa et al, 1988;Herrera et al, 2002;Ye et al, 2013). Owl monkeys are susceptible to human and nonhuman LABORATORY ANIMAL MEDICINE primate malarias and can transmit these infections to mosquitoes.…”
Section: Research Usesmentioning
confidence: 99%
“…Owl monkeys have been used extensively in the study of malaria, including maintenance of various malarial strains, antigen production, studies of host-vector relationships, parasite life-cycles, and potential therapeutics (Aikawa et al, 1988;Herrera et al, 2002;Ye et al, 2013). Owl monkeys are susceptible to human and nonhuman LABORATORY ANIMAL MEDICINE primate malarias and can transmit these infections to mosquitoes.…”
Section: Research Usesmentioning
confidence: 99%
“…Recently, we have demonstrated that tetrandrine (a bisbenzyl isoquinoline) in combination with chloroquine can cure chloroquineresistant-falciparum malaria in Aotus monkeys if given over a several week period [24]. Since we know that tetrandrine can boost the antimalarial activity of chloroquine over 40 fold in a chloroquineresistant falciparum malarial strain [2], and since tetrandrine has a long biological half-life (weeks) in man and monkeys, our studies in Aotus should not be particularly surprising.…”
Section: Resultsmentioning
confidence: 96%
“…Since the model has been developed upon the inhibitors of AMA1‐RON2 interaction, we feel an important achievement of this work is to produce a testable hypothesis for experimental biologists to find out whether, in addition to other possible mechanisms, these compounds work as anti‐malarials by inhibiting interaction of AMA1 and RON2. We feel this is relevant as Tetrandrine has been recently shown to work even on Chloroquine resistant strains of P. Falciparum in Aotus monkeys 37a. As Quinines target intra‐erythrocytic stage therefore a strong possibility exists that Tetrandrine works by a different mechanism.…”
Section: Discussionmentioning
confidence: 97%